New data on the genus Wiedemannia Zetterstedt (Diptera: Empididae) from the Caucasus with description of four new species - Kustov, Semen; Zherebilo, Danil (Zootaxa, 2015)
Currently, 17 species of aquatic dance flies of the genus Wiedemannia are known from the Caucasus including four new species: W. ivkovicae sp. nov. (South Ossetia), W. nartshukae sp. nov. (South Ossetia), W. ossetiana sp. nov. (South Ossetia) and W. pseguashae sp. nov. (Georgia, South Ossetia). Wiedemannia (Chamaedipsia) lota Walker 1851 (Russia; Georgia) is recorded from the Caucasus for the first time. The inaccuracies in species records from the different countries of the Caucasus have been eliminated. Nine species are recorded for the first time from the territory of Georgia, five species for Abkhazia and one for Russia. The new species are described, all species illustrated and distribution listed. A key to species of Wiedemannia from the Caucasus is provided.